Implementing and using a patient portal: a qualitative exploration of patient and provider perspectives on engaging patients. Issue 2 (1st April 2016) - Ryan, Bridget L.; Brown, Judith Belle; Terry, Amanda; Cejic, Sonny; Stewart, Moira; Thind, Amardeep
Abstract : Background: The use of portals might be expected to rise; however, adoption has been slow. Development of portals has occurred with limited patient involvement. This paper fills a need for literature concerning perspectives regarding the value of portals, how best to organize and provide portals and critically how to seek patient involvement in implementation. Objective: The objective was to explore the feelings, ideas, and expectations of patients and primary care providers concerning the implementation and use of patient portals. Methods: The study employed a descriptive qualitative design interviewing seven patients and four providers from an interdisciplinary primary health care clinic in Ontario, Canada. Patients were older with at least one chronic condition. Interviews were analysed independently by three coders who then met to synthesize the findings. Results: There was limited experience of portals and substantial convergence between patients and providers regarding concerns and potential benefits with an overall positive view. Four themes emerged: 1) the context in which patient portal use takes place; 2) the necessary conditions for use of a patient portal; 3) the implementation of a patient portal and 4) the use of a patient portal for care. Conclusion: Findings highlight that it is not sufficient to engage patients in the use of a portal; it is critical that patients be engaged in the early stages of implementation. With many health and fitness electronic tools available (e.g. Fitbit), this study reminds us that tools are not enough. Patient engagement requires patient-centred partnerships between patients and health care providers.